2009
DOI: 10.1111/j.1365-2109.2009.02197.x
|View full text |Cite
|
Sign up to set email alerts
|

Biotransformation of tuna waste by co-fermentation into an aquafeed ingredient

Abstract: Dried skipjack tuna (Katsuwonus pelamis) waste (red meat, gills, viscera, ¢ns, etc.) ). Changes in the nutritional quality (crude protein, crude fat, crude ash, crude ¢bre and nitrogen-free extract and aminoacids) were monitored during a fermentation period of14 days. The proximate analysis showed signi¢cant changes in the composition of L. plantarum-fermented tuna (LPFT) and B. licheniformis-fermented tuna (BLFT) from the unfermented raw materials. Fermentation of tuna waste has resulted in a signi¢cant (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…In an experiment conducted by Vijayan et al ., increased CP was observed in tuna waste when fermented with wheat flour and Lactobacillus plantarum . Furthermore, Geron et al .…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…In an experiment conducted by Vijayan et al ., increased CP was observed in tuna waste when fermented with wheat flour and Lactobacillus plantarum . Furthermore, Geron et al .…”
Section: Resultsmentioning
confidence: 97%
“…is reported . The increase in NPN and TVN occurs due to the enzymatic cleavage of the protein fraction by the activities of proteolytic enzymes . The decrease in NPN and TVN during bacterial fermentation is generalized to using these compounds by microorganisms …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the amino acid levels, particularly for lysine (5.9% of diet) and methionine (2.6% of diet) (Hernández et al ), in tuna byproduct meal are higher than in FTBM (lysine: 4.85%, methionine: 1.46% of diet). It has been reported as well that fermentation of the fishery byproducts and plant protein mixture could improve its nutritional profile (Vijayan et al ), thereby allowing higher inclusion levels in fish diets. Kader et al () found that 36% of FM could be substituted with the blend of fermented soybean meal and scallop byproduct in the diet of red sea bream, P. major .…”
Section: Discussionmentioning
confidence: 99%
“…Yoon et al (1997) described the characteristics of LAB for the preparation of silage from tuna viscera. Successful studies have been performed on biotransformation of salmon (Bower and Hietala, 2008) and tuna waste (Vijayan et al, 2009) as novel aquafeed ingredient for fish.…”
Section: Fermentationmentioning
confidence: 99%